Sources and Distribution of Polycyclic Aromatic Hydrocarbons (PAHs) in Sediment Core of Khor Al-Zubair: Sumber dan Distribusi Hidrokarbon Aromatik Polisiklik (PAH) di Inti Sedimen Khor Al-Zubair - Abo-Turab , Fatima Fakhir; Mohammed , Abbas Hameed; Al-Saad , Hamid Talib (Indonesian Journal on Health Science and Medicine, 2024)
Hydrocarbon pollution is related to the pollution of the environment by hydrocarbons, organic compounds that include hydrogen and carbon, which occur naturally in various forms. Crude oil and natural gas are significant hydrocarbon sources utilized for energy,which is one of the most important causes of pollution. The source and distribution of PAHs has been studied in core sample in Khor Al-Zubair, Basrah southern Iraq. Sediment samples were taken from 5 station. The sediment was extracted and the PAHs were determined by Gas chromatography mass (GC-Mass). The average of total PAHs concentrations ranged frome 31.31 to 157.901 ng/g. The study contributed to revealing the pollution levels in the study area, as the result indicated that most components originate from a petrogenic source. This study gave a baseline on the source and distribution of these components in the Khor Al-Zubair area of Basra Governorate and can be used as a baseline for future studies Highlights: Hydrocarbon pollution: Environmental contamination from crude oil and natural gas. Study area: PAHs analyzed in Khor Al-Zubair sediments using GC-Mass. Findings: PAHs (31.31–157.901 ng/g) mainly from petrogenic sources. Keywords: polycyclic aromatic hydrocarbons, PAHs, sediment pollution, Khor Al-Zubair, Basrah governorate.